Investigation of the Biological Activities of Different Extracts from Dipsacus laciniatus Aerial Parts - Taşkın, Turgut; Akkılıç, Yeliz; Çelik, Berna Özbek; Şenkardeş, İsmail and Özakpınar, Özlem B. (Natural Products Journal, The, 2020)
Background: The aerial parts of Dipsacus laciniatus are traditionally used in the treatment of colds as cold tea; decoction prepared from its roots and aerial parts are used for the treatment of diabetes and cancer, respectively. The extraction procedures and solvents are important steps in the processing of bioactive constituents from the plant materials. Objective: The aim of this study was to evaluate in vitro antioxidant, antimicrobial, anticholinesterase and cytotoxic activities for the first time in plant’s different extracts. Methods: The antioxidant activities of extracts were examined using FRAP and CUPRAC methods, including total phenolic and flavonoids contents. In addition, the antimicrobial, anticholinesterase and cytotoxic activities of extracts were investigated using microdilution, Ellman and MTT methods, respectively. Results: In the present study, methanol extract showed stronger iron (III) ion reduction (FRAP) and copper (II) ion reducing antioxidant capacity (CUPRAC) than other extracts and also contained higher total phenolic and flavonoid compounds. It was also found that there was a linear relationship between antioxidant activity and phenolic compounds in this study. It was demonstrated that the chloroform and methanol extracts showed moderate antimicrobial activity against S. epidermidis and C. albicans strains. The chloroform extract had a strong and selective cytotoxic activity for the MCF-7 and HT-29 cell lines, while the methanol extract showed low cytotoxic activity on the same cell lines. In addition, according to the obtained data, chloroform extract showed a toxic effect on normal cell line (NIH/3T3), but other extracts showed no toxic effect. Conclusion: Since methanol extract has no toxic effect on normal cell line and has strong antioxidant, anticholinesterase and antimicrobial activity, it is thought that this extract may be useful as an antioxidant, anticholinesterase and antimicrobial agents in the future.
Keywords: antioxidant